Hypocrisy in George Orwellâs Animal Farm: An Islamic Analysis - Ali, R. Muhammad (Ahmad Dahlan Journal of English Studies, 2015)
This article is taken from a research entitled Hypocrisy in George Orwellâs Animal Farm: an Islamic Analysis. ItÂ  is intendedÂ  : (1) to describe the concept of hypocrisy in the view of Islam, (2) to describe the traits of a hypocrite in Islamic view, and (3) to reveal the hypocrisy of the characters of the novel.Â Â Â Â Â Â Â Â Â Â Â  The research is categorized as library research in which the data are taken from books, journals, and other relevant data. This is also a descriptive qualitative research with Islamic approach. The base and concept of hypocrisy are from the verses of the Holy Qurâan and the hadiths of the Messenger Muhammad (sas).Â Â Â Â Â Â Â Â Â Â Â  The results of the research are: First, the definition of hypocrisy is a pretending to be what is not; to feel what one does not feel; especially pretense of virtue, piety, etc.Â  Second, The traits of a hypocrite are: (a) when he/she speaks he/she lies, (b) when he/she promises he/she breaks his/her promise, and (c) when he/she is entrusted he/she betrays. Third, the behaviors of the characters of Animal Farm that represent hypocrisy are: (a) Napoleon, the main character, always lies and changes the black into white, (b) Napoleon always breaks the agreement among the animals, and (3) the pigs betray the power they have entrusted.Â Keywords: hypocrisy, Animal Farm, islamic analysis